Estudo do perfil antropométrico, estilo de vida e comportamento sexual de adolescentes do programa saúde na escola - Cirqueira, Denise Soares de (2014)
Adolescence is a stage of development, marked by important changes in biopsychosocial nature, from which originate the specific needs and demands of health. Healthcare practices have shown the difficulty in linking the teens to health services. After the implementation of the School Health Program, comes an important social space for the development of comprehensive and effective care practices adolescent health. We seek to investigate the anthropometric profile, lifestyle and sexual behavior of adolescent School Health Program in Goiania – Goias. This is a cross-sectional study among 1171 adolescents between 10 and 19 years old, enrolled in public institutions education, participants in the School Health program. We used a questionnaire protocol recommended by the Pan American Health Assistance Organization, and the analysis used the Statistical Package for the Social Sciences 17.0. Anthropometric assessment was interpreted by Anthro-Plus-2007 software. The results show that of 1171 adolescents, 610 were male and 561 were female, and 54.8% were aged between 10-14 years. Most respondents had lower weight (74.3%) and height (94.1%) suitable for age. Note that 20.9% of adolescents were overweight; performed 4 to 6 meals per day (72.6%), with 3 meals took place in the presence of family (91.7%). The average of first sexual intercourse was 13.8 years. As for the number of sexual partners among boys was more often there are multiple partners (10%), while girls predominated single partner (15.9%). Affection for some Sexually Transmitted Disease was more common among adolescents (0.9%). The results allow to know the prevalence of health risk factors of adolescents, generating evidence to inform the development of health promotion activities in the school environment, contributing to improving the quality of life of adolescents.